Economic structural adjustment programmes in the Southern African development community : an analysis of impact and policy considerations with special reference to Zambia and Zimbabwe - Gumede, Nyawo Basirio Simbi (Department of Political Studies, 2014)
Bibliography: leaves 183-189.